EFEKTIVITAS PEMANFAATAN MEDIA PAPAN STATISTIKA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VI SEKOLAH DASAR - Rafika Dian Rahmawati; Isna Hidayat; Iin Wahyuni; Budi Murtiyasa; Sumardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to evaluate the effectiveness of improving learning outcomes in mathematics of grade VI SDN 03 Jaten by using statistical board media on the topics of mean, mode, and median. In a quantitative method and quasi-experimental design, 24 students from SDN 03 Jaten were divided between experimental and control groups. The results of the pre-test analysis showed that both groups had the same initial ability. However, after the intervention, students in the experimental group achieved an average score of 78.5, while the control group was only 62.3. The t-test results showed a significant difference between the two groups with a p-value <0.05. This shows that the use of statistics board media is effective in improving students' understanding of statistics material. Thus, it is recommended to integrate this innovative media in mathematics learning in elementary schools.